β-cell Heterogeneity: The Key to β-cell Replacement Therapy - Ercument Dirice (Pancreas, 2016)
Pancreatic islets of Langerhans are cell clusters that play a key role in glucose homeostasis. Among the five hormone secret-ingislet endocrine cells (insulin secreting β-cells, glucagon secret-ing α-cells, somatostatin secreting δ-cells, pancreatic polypeptide secreting PP-cells, and ghrelin secreting ε-cells), β-cells are special-ized glucose sensors that respond to increased insulin demand dur-ing physiological (i.e. pregnancy) or pathophysiological (i.e. type 2 diabetes) conditions.